COGNITIVE, AFFECTIVE AND CONATIVE MODEL FOR ANALYSING HIGHER EDUCATION STUDENTSq - MANICKAVASAGAM, PRIYAADHARSHINI; Surwade, Swati S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Many models are used in recent years to analyze behavior of the students in the higher education. Analyzing the learning style and student performance in academic studies are very essential to enhance their performance. This research work is focused on analyzing the learners behavior using three dimensions, i.e., cognitive, affective, and conative model. In this paper, we used Moodle learning management system which is a learning platform to create a personalized learning environment and to track learning abilities using activities. This model will be helpful to study the cognitive, conative, and emotions of students. Â